2009
DOI: 10.3174/ajnr.a1859
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perfusion CT of Advanced Squamous Cell Carcinoma of the Head and Neck Treated during the Course of Concomitant Chemoradiotherapy

Abstract: BACKGROUND AND PURPOSE:Concomitant chemoradiation is a promising therapy for the treatment of locoregionally advanced head and neck carcinoma. The purpose of this study was to prospectively evaluate early changes in primary tumor perfusion parameters during concomitant cisplatin-based chemoradiotherapy of locoregionally advanced SCCHN and to evaluate their predictive value for response of the primary tumor to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
(25 reference statements)
3
39
2
Order By: Relevance
“…11 The fluctuations in perfusion parameters in patients with HNSCC at the different dose points may be similar to those in animal models of tumor response to fractionation, demonstrating that the oxygenation of the tumor is constantly changing as oxygenated cells depopulate and hypoxic areas reoxygenate after each radiation dose. 11 Surlan-Popovic et al 6 additionally showed that a nonsignificant increase in BF, BV, and CP was seen in patients with LRF at 40 and 70 Gy, which was difficult to ascertain from our study due to the limited number of treatment failures and decreasing number of scans at weeks 4 and 6 of treatment.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…11 The fluctuations in perfusion parameters in patients with HNSCC at the different dose points may be similar to those in animal models of tumor response to fractionation, demonstrating that the oxygenation of the tumor is constantly changing as oxygenated cells depopulate and hypoxic areas reoxygenate after each radiation dose. 11 Surlan-Popovic et al 6 additionally showed that a nonsignificant increase in BF, BV, and CP was seen in patients with LRF at 40 and 70 Gy, which was difficult to ascertain from our study due to the limited number of treatment failures and decreasing number of scans at weeks 4 and 6 of treatment.…”
Section: Discussioncontrasting
confidence: 42%
“…In the current study, most patients underwent IMRT by using a simultaneously integrated boost or "dose-painted" technique, while in the study by Surlan-Popvic et al, 6 all patients underwent 3D conformal RT. This method of IMRT results in a more heterogeneously delivered radiation-dose distribution to the tumor compared with 3D conformal radiation therapy, which delivers a uniform dose distribution, and this may be a contributing factor to the variation in our CTP results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of their report showed the same trend as that seen in the present study in regard to the patients who achieved SD status. In contrast, Surlan-Popovic et al 15 and Gandhi et al 16 reported that the follow-up TBF values during chemoradiotherapy were significantly lower in the patients with a good treatment response compared with those with a poor response, though more delayed timing was used in the study by Surlan-Popovic et al 15 (the point of 40 Gy in a total of 65 Gy of radiation therapy) and the study by A, Subgroup analysis of patients in the SD group (the patients with Յ30% TV reduction in the early treatment period); the percentage change of TBF in the failure group (Ϫ0.9% Ϯ 11.9%) was significantly lower than that in the local control group (23.0% Ϯ 17.2%) (P Ͻ .01) (*); the best diagnostic accuracy of 0.94 (16/17) with sensitivity of 1.0 (10/10) and specificity of 0.86 (6/7), with the threshold value 7% (**) was revealed by receiver operating characteristic analysis. B, Subgroup analysis of the PR patient group (the patients with Ͼ30% TV reduction in the early treatment period); the percentage change of TBF in the failure group (Ϫ9.2% Ϯ 9.7%) was significantly higher than that in the local control group (Ϫ35.1% Ϯ 21.0%) (P Ͻ .01) (*).…”
Section: Discussionmentioning
confidence: 91%
“…12,13 Because of the difficulties of repetitive scanning, there have been few studies of the changes in TBF with repetitive scanning over the treatment period, and the number of patients in these reports is quite small, at 10 to Ͻ20 patients. [14][15][16] Thus, the role and potential of TBF measurement during treatment remain unclear. TBF measurement by pseudocontinuous arterial spinlabeling (pCASL), which was introduced for the noninvasive measurement of tissue blood flow without the need for a contrast agent and with no radiation exposure, 17,18 was recently demonstrated to be feasible and applicable for HNSCCs 19 ; pCASL thus has potential for the evaluation of treatment effects in patients with HNSCC without the risks with repetitive scanning of contrast-induced nephropathy during chemotherapy and increased radiation exposure.…”
mentioning
confidence: 99%